CULTURAL LINGUISTICS AND COGNITIVE INTERPRETATION OF COLOR TERMS: THE SEMANTIC AND SYMBOLIC POTENTIAL OF RED AND BLUE - Utepbergenova, D. (SCIENCE and SOCIETY, 2026)
This article examines the semantic and symbolic potential of the color terms red and blue within the framework of cognitive linguistics and cultural linguistics. The results demonstrate that red and blue exhibit a core–periphery semantic structure and reflect both universal cognitive mechanisms and culture-specific conceptualizations.